Vitamin D Deficiency in Childhood: A Review - Saadon, Hanan (University of Thi-Qar Journal of Science, 2024)
Vitamin D is primarily obtained through sun exposure and diet, but factors like dark skin tone, limited time outside, and poor dietary habits can contribute to low levels of this essential vitamin. Getting enough Vitamin D is really important for kids' health, but a lot of them don't get enough because they don't spend enough time in the sun, don't eat well, or have trouble absorbing it. Not having enough can cause weaker bones, more infections, long-term illnesses, and problems with the immune system. To avoid this, children need to spend more time in the sun, eat foods rich in Vitamin D, and maybe take some supplements as well. In summary, this review highlights the importance of addressing vitamin D deficiency in children for their overall health and well-being.